Densification mechanism and structural transformation in glass: molecular dynamic simulation - Thi Thanh Ha, Nguyen (VNU Journal of Science: Mathematics - Physics, 2024)
The structure of GeO 2 glass is investigated via molecular dynamic simulation. The influence of pressure to the structure of GeO 2 glass is due to the change of short-range order, network structure, domain structure and free volume regions. The obtained results show that the structure of GeO 2 was formed by a continuous random network of basic structural units linking to each other via with corner-sharing, edge-sharing, face-sharing bond. At low pressure, the basic structural units are mainly linked via one bridge oxygen (the corner sharing bonds). As pressure increases, the fraction of edge sharing bonds (two bridge oxygen) increases meanwhile the fraction of corner sharing bonds significantly decrease. There is a slight increase with the fraction of face- sharing bonds (three bridge oxygen). The Ge-O bond distance is almost not dependent on pressure, meanwhile the Ge-Ge and O-O bond distances are significantly dependent on pressure. Under compression, the average coordination number of Ge tends to increase from fourfold (at ambient pressure) to six-fold (at high pressure). Moreover, structure of GeO 2 glass has two-domain near 15 and 25 GPa. And at ambient pressure or high pressures, the struture of GeO 2 glass has single domain. The dependence of the distribution of free volumes on pressure in GeO 2 glass has been examined. The distribution of void radius has the Gaussian form and the position of the peak tend to shift to the left under compression.